Aesthetics in Kitsch art: the aesthetic ideology and teleological purpose behind the charged sentimentality. - Yasmine Gamal Abdrabbo; Cherine Gamal Abdrabbo (ESPES)
This article addresses the problem of perceiving Kitsch art and elaborates on the philosophical approaches taken to better understand all intellectual contexts surrounding the term, aiming to endorse its aesthetic aspect and assert its rightness to be subsumed under the notion of high art, the researchers sought to argue that besides the claim that the main issue of reading Kitsch was laid on miss-perceiving it, by means it was a problem of perception, we add to this assertion that it was also a problem of misinterpretation, that critics have constrained their judgments on Kitsch art by narrowed and prejudiced contentions while many aesthetic theories can ascertain its aesthetic existence at the time, and the most crucial one is the theories on aesthetic emotions, for it was the emotional charge of Kitsch paintings which the critics used to reject and vastly criticize to deny its ability to conceive any aesthetic features.